Rancang Bangun Aplikasi Pengenalan Rukun Islam Sebagai Media Pembelajaran Menggunakan Teknologi Augmented Reality - Asri Mulyani; Dede Kurniadi; Mahendra Akbar Musadad (Institut Teknologi Garut, 2021)
The main points of Islamic teachings are the pillars of Islam and are also the guidelines of a Muslim such as saying the shahada, praying, zakat, fasting, and going on the pilgrimage. Learning about the pillars of Islam in schools is often conveyed through books which sometimes create a bored effect to increase interest in learning in children when learning activities are not allowed to do face-to-face due to the COVID-19 pandemic situation, therefore the learning is packaged more attractively by including multimedia elements. This study aims to create an application for the introduction of the pillars of Islam using augmented reality which is a variation. the benefit of this research is that it can be used as a learning medium that attracts children's interest in learning the pillars of Islam, especially reading and prayer movements and as a tool for teachers in delivering learning about the pillars of Islam. Making this application using the Research And Development methodology with the stages of analysis, data collection, design design, design implementation, testing, expert validation, revision, feasibility test, media and product improvement. The results of this study are the application of the introduction of the pillars of Islam as a learning medium using augmented reality with the androidI platform to operate it.